Of idolatrias Hernando de Noboa: Cajatambo, 17th century - south of Ancash 21st century - Robles Mendoza, Román (2020)
In this work we do a contemporary review of the continuity and disappearance of the peoples visited by Don Bernardo de Noboa in the seventeenth century, in his mission to extirpate the idolatry of the Indians of the Cajatambo region. This ecclesiastical enterprise was undertaken more than a century after the Spanish conquest, when the efforts of the Christianization of natives had failed throughout the Castilian dominion. The Archbishopric of Lima, -from Bartolomé Lobo Guerrero to Pedro de Villagómezundertook, in stages, a policy of persecution and punishment of the Andean priests, and the destruction of the sacred idols of the vanquished peoples, with the purpose of nipping the roots of the Andean belief system and deepen the evangelization in the conscience of the natives. At that time, the towns through which the extirpating commission traveled, was the northern part of Cajatambo, mainly the localities attached to the pre-Hispanic parish chaupihuaranga of Ticllos. We present this comparative work of the Andean peoples of the region, ancient and current, with the data provided by the colonial documents and the ethnography of the region worked by the author, during the last decades of these times.